2023
DOI: 10.1021/acsami.2c17877
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution In Situ High-Content Imaging of 3D-Bioprinted Single Breast Cancer Spheroids for Advanced Quantification of Benzo(a)pyrene Carcinogen-Induced Breast Cancer Stem Cells

Abstract: Cancer stem cells (CSCs), also known as tumor-initiating cells, are critically correlated with carcinogenesis and are strongly affected by the environmental factors. Environmental carcinogens, such as benzo(a)pyrene (BaP), are associated with the overproduction of CSCs in various types of cancers, including breast cancer. In this report, we present a sophisticated 3D breast cancer spheroid model for the direct identification and quantitative determination of CSCs induced by carcinogens within intact 3D spheroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…The study employed a mouse model induced with benzo­( a )­pyrene compounds (BAP) to assess further the therapeutic effectiveness of developing cancer. BAP, a polycyclic aromatic hydrocarbon (PAH), is known for its exceptionally high carcinogenic potential. , This propensity arises from the metabolic conversion of PAH compounds in the body into diol epoxides, , which subsequently bind to DNA and initiate the carcinogenic process. The results demonstrated that the B-CDs/Naproxen group exhibited a significant decrease in malignancy diameter throughout the study, while the control group showed a notable increase in cancer size volume.…”
Section: Discussionmentioning
confidence: 99%
“…The study employed a mouse model induced with benzo­( a )­pyrene compounds (BAP) to assess further the therapeutic effectiveness of developing cancer. BAP, a polycyclic aromatic hydrocarbon (PAH), is known for its exceptionally high carcinogenic potential. , This propensity arises from the metabolic conversion of PAH compounds in the body into diol epoxides, , which subsequently bind to DNA and initiate the carcinogenic process. The results demonstrated that the B-CDs/Naproxen group exhibited a significant decrease in malignancy diameter throughout the study, while the control group showed a notable increase in cancer size volume.…”
Section: Discussionmentioning
confidence: 99%